France (International Monetary Fund, 2022)
A strong economic recovery is underway in France, bolstered by progress on vaccination, strong fiscal support and solid private sector led investment. Employment has recovered to above pre-crisis levels and unemployment is virtually stable. Inflation is increasing, mainly driven by a rise in energy prices but also due to supply-chain disruptions. The public deficit and debt ratio surged in 2020, reflecting the large amount of emergency support deployed and the drop in activity
10.5089/9798400201172.002
Keywords: Graue Literatur; IMF staff calculation; government shares staff view; des coûts; day infection rate; debt ratio; headline inflation; Global; Europe; Labor markets; Inflation; International Agreements and Observance; International Organizations; Monetary Policy; International Economics; Statistics; Financial Risk Management; Public Finance; Financial Crises; Debt; Debt Management; Sovereign Debt; Demand and Supply of Labor: General; Price Level; Deflation; Data Collection and Data Estimation Methodology; Computer Programs: Other; Monetary economics; International institutions; Public finance & taxation; Labour; income economics; Economic & financial crises & disasters; Macroeconomics; Finance; International organization; Public debt; Money and Monetary Policy; Labor; Expenditure; Monetary policy; International agencies; Financial crises; Debts; Public; Labor market; Prices; Financial services industry